The significance of kinesiotaping in the rehabilitation of patients after orthognathic surgery - R. I. Slabkovsky; N. S. Drobysheva; A. B. Slabkovskay (Эндодонтия Today, 2025)
INTRODUCTION. Orthognathic surgery aims to restore the anatomical shape, spatial position of the mandible, and normalize its functions, thereby improving facial aesthetics and patients’ quality of life. However, the postoperative period is often accompanied by complications such as edema, pain syndrome, decreased sensitivity, and soft tissue induration. Currently, there is a lack of systematic data on early postoperative recovery, highlighting the need for new rehabilitation methods.Kinesiotaping has proven to be an effective nonpharmacological technique that reduces edema and hematomas, regulates the tone of masticatory muscles, improves microcirculation, and accelerates rehabilitation. Its mechanism of action is based on the stimulation of skin and fascial receptors, promoting pain relief and muscle function recovery. This study aims to assess the effectiveness of kinesiotaping in patients undergoing orthognathic surgery.AIM. To analyze the effects of kinesiotaping on the rehabilitation process of orthodontic patients after orthognathic surgery.MATERIALS AND METHODS. The study included 20 patients who underwent unilateral kinesiotaping (left side) in the postoperative period. To assess postoperative edema severity, facial symmetry was analyzed using frontal photographs, measuring facial width indices at various anatomical landmarks (Fr-Fl, Zyl-Zyr, Nml-Nmr, Ncl-Ncr, Gol-Gor) on the 1st, 2nd, and 7th postoperative days.Functional diagnostics of the maxillofacial muscles included myotonometry and electromyography (EMG). Myotonometry measured the tone of the masticatory muscles at rest and during maximal voluntary contraction, comparing the results with normative values. EMG analyzed the bioelectrical activity of the temporal, masseter, suprahyoid, and sternocleidomastoid muscles. The assessment was conducted using ARV (Averaged Rectified Value) and RMS (Root Mean Square) parameters at rest and during maximum occlusion.RESULTS. Maximum edema was observed on the 2nd postoperative day, but it was less pronounced in the kinesiotaping group: a 20% reduction in the nasal wings area and a 17% reduction in the lower face. By the 7th day, edema decreased more significantly on the taped side. Myotonometry showed a preoperative difference in masticatory muscle tone of 11.9% between the sides. After kinesiotaping, tone normalization was faster – reducing the difference by 64.1% compared to 7.1%. EMG analysis revealed that on the 7th postoperative day, bioelectrical activity in untaped muscles exceeded normal values (masseter: +83.8%, temporal: +112%). On the taped side, EMG readings were closer to normal, and by the 21st day, they had fully stabilized. Kinesiotaping effectively reduces postoperative edema, normalizes muscle tone and bioelectrical activity, and accelerates rehabilitation.CONCLUSIONS. In the early postoperative period, kinesiotaping using a fascial technique without pressure alleviates pain, restores muscle function, and facilitates the resumption of orthodontic treatment, ultimately reducing overall rehabilitation time.